PENGARUH KOMBINASI ARANG TEMPURUNG KELAPA DAN ABU SEKAM PADI TERHADAP PERBAIKAN SIFAT KIMIA TANAH SAWAH SERTA PERTUMBUHAN TANAMAN JAGUNG - Andreas Priyo Handoko; Kurniawan Sigit Wicaksono; M Lutfi Rayes (Departemen Tanah, Fakultas Pertanian, Universitas Brawijaya, 2016)
During dry seasons, paddy soils are usually deficit or shortage of water that in turn affecting chemical properties of the soils. The aim of this studyÂ was to look for the effects of coconut shell charcoal and rice husk ash on the improvement of soil properties and growth and yield of maize. The study was conducted in Nganjuk and basic soil analysis was carried out at the Faculty of Agriculture, Brawijaya University. The experimental method used two factors. The first factor was the dose of rice husk ash which consisted of four levels i.e. without husk ash (A0), rice husk ash 50 g polybag-1 (A1), rice husk ash 100 g polybag-1 (A2), and rice husk ash 150 g polybag-1 (A3). The second factor was the dose of coconut shell charcoal which consisted of four levels i.e. without coconut shell charcoal (B0), coconut shell charcoal 50 g polybag-1 (B1), coconut shell charcoal 100 g polybag-1 (B2), and coconut shell charcoal 150 g polybag-1 (B3). Based on the results of the analysis showed that the application did not show significant effect of the two parameters, namely chemical properties and plant growth. But at the treatment of 150 gÂ polybag-1 coconut shell and husk ash significantly increased the pH value to 5.7.